H. ASAN SAMPIT AIRPORT DEVELOPMENT: AIR TRANSPORTATION INFRASTRUCTURE STRATEGY FOR THE GROWTH OF THE CENTRAL KALIMANTAN REGION - hanafie Adhie Prakoso; Febria Roza; Axel Yuan Andry Sihite; Gilang Ardiansyah; Ferri Amsar Tauna; Farhandito Hasto Utomo; Divan Aprilian Budi Pangestu (DEARSIP : Journal of Architecture and Civil, 2025)
The development of H. Asan Sampit Airport is a strategic step to support increased mobility, economic growth, and regional connectivity in East Kotawaringin Regency. Based on the analysis of demand projections, the number of passengers is expected to increase to 2,300 passengers per day by 2035, or an increase of more than 90% compared to 2018 conditions. However, the current infrastructure condition is inadequate, characterized by a PCN value of only 24/F/C/X/T, well below the minimum standard of 45–50 required for a large body aircraft such as the Airbus A320. This study uses descriptive qualitative methods and Fishbone analysis to identify the root of the problem which includes human aspects, methods, machines, materials, environment, and management. The results of the study show the need to increase the runway to 2,250–2,400 meters, increase the PCN, expand the terminal, and modernize facilities according to ICAO Annex 14 standards. With the right infrastructure and managerial interventions, H. Asan Airport has the potential to increase the regional economic contribution by 0.8–1.3% of GDP per year.